Evaluation of the In Vitro Antiparasitic Effect of the Essential Oil of Cymbopogon winterianus and Its Chemical Composition Analysis - Pedro Silvino Pereira; Carlos Vinicius Barros Oliveira; Ana Josicleide Maia; Maria Celeste Vega-Gomez; Miriam Rolón; Cathia Coronel; Antônia Eliene Duarte; Henrique Douglas Melo Coutinho; Abolghasem Siyadatpanah; Roghayeh Norouzi; Seyed Jafar Adnani Sadati; Polrat Wilairatana; et al. (Molecules, 2022)
Cymbopogon winterianus, known as “citronella grass”, is an important aromatic and medicinal tropical herbaceous plant. The essential oil of C. winterianus (EOCw) is popularly used to play an important role in improving human health due to its potential as a bioactive component. The present study aimed to identify the components of the essential oil of C. winterianus and verify its leishmanicidal and trypanocidal potential, as well as the cytotoxicity in mammalian cells, in vitro. The EOCw had geraniol (42.13%), citronellal (17.31%), and citronellol (16.91%) as major constituents. The essential oil only exhibited significant cytotoxicity in mammalian fibroblasts at concentrations greater than 250 μg/mL, while regarding antipromastigote and antiepimastigote activities, they presented values considered clinically relevant, since both had LC50 < 62.5 μg/mL. It can be concluded that this is a pioneer study on the potential of the essential oil of C. winterianus and its use against the parasites T. cruzi and L. brasiliensis, and its importance is also based on this fact. Additionally, according to the results, C. winterianus was effective in presenting values of clinical relevance and low toxicity and, therefore, an indicator of popular use.